Factors associated with disease progression in early-diagnosed pulmonary arterial hypertension associated with systemic sclerosis: longitudinal data from the DETECT cohort - Mihai, Carina; Grünig, Ekkehard (Annals of the rheumatic diseases, 2018)
Objective Pulmonary arterial hypertension (PAH) is a severe complication of systemic sclerosis (SSc). In this longitudinal study, we aimed to identify factors associated with an unfavourable outcome in patients with SSc with early PAH (SSc-PAH) from the DETECT cohort. Methods Patients with SSc-PAH enrolled in DETECT were observed for up to 3 years. Associations between cross-sectional variables and disease progression (defined as the occurrence of any of the following events: WHO Functional Class worsening, combination therapy for PAH, hospitalisation or death) were analysed by univariable logistic regression. Results Of 57 patients with PAH (median observation time 12.6 months), 25 (43.9%) had disease progression. The following factors (OR (95% CI)) were associated with disease progression: male gender (4.1 (1.2 to 14.1)), high forced vital capacity % predicted/carbon monoxide lung diffusion capacity (DLCO)% predicted ratio (3.6 (1.2 to 10.7)), high Borg Dyspnoea Index (1.7 (1.1 to 2.6)) and low DLCO% predicted (non-linear relationship). Conclusion More than 40% of early-diagnosed patients with SSc-PAH had disease progression during a short follow-up time, with male gender, functional capacity and pulmonary function tests at PAH diagnosis being associated with progression. This suggests that even mild PAH should be considered a high-risk complication of SSc.
Published online first 23 October 2017
Gesehen am 31.10.2018